Prime Archives in Neuroscience 2020
DOI: 10.37247/pans.1.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol (CBD) Inhibited Rhodamine-123 Efflux in Cultured Vascular Endothelial Cells and Astrocytes under Hypoxic Conditions

Abstract: Despite the constant development of new antiepileptic drugs (AEDs), more than 30% of patients develop refractory epilepsy (RE) characterized by a multidrug-resistant (MDR) phenotype. The -transporters hypothesis‖ indicates that the mechanism of this MDR phenotype is the overexpression of ABC transporters such as P-glycoprotein (P-gp) in the neurovascular unit cells, limiting access of the AEDs to the brain. Recent clinical trials and basic studies have shown encouraging results for the use of cannabinoids in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…87 Several mechanisms have been proposed by which cannabinoids could exert their beneficial effects for the most severe types of epilepsy. 88,89 By docking studies, our group recently demonstrated that cannabidiol has binding sites on P-gp and induces an inhibitory effect on the efflux transport of Rho-123 (a P-gp substrate) in cultured cells, 90 such as that induce by nimodipine. 52 This finding gives molecular consistency to the efficacy of cannabidiol (as adjuvant therapy) in the control of most severe refractory epilepsies.…”
Section: Glycoprotein In the Heart And Its Potential Role In Sudep De...mentioning
confidence: 99%
“…87 Several mechanisms have been proposed by which cannabinoids could exert their beneficial effects for the most severe types of epilepsy. 88,89 By docking studies, our group recently demonstrated that cannabidiol has binding sites on P-gp and induces an inhibitory effect on the efflux transport of Rho-123 (a P-gp substrate) in cultured cells, 90 such as that induce by nimodipine. 52 This finding gives molecular consistency to the efficacy of cannabidiol (as adjuvant therapy) in the control of most severe refractory epilepsies.…”
Section: Glycoprotein In the Heart And Its Potential Role In Sudep De...mentioning
confidence: 99%